Corporate governance research: A review of qualitative literature - Mat Yasin, F.; Muhamad, R.; Sulaiman, N.A. (2014)
The focus on corporate governance has increased since the past few decades in most countries around the world, especially in the wake of corporate collapses in early 2000s. These corporate collapses have leads to the growing volume of academic and practical research in this area. Although the quantitative literature on corporate governance is diverse and extensive, the qualitative research in this area is rather limited. This paper provides a review of prior qualitative research on the corporate governance to guide future research on corporate governance. Qualitative study method allows the researcher to gather rich information in this area